The molecular characterisation of sol-gel biocatalysts - Rodgers, Lisa Elizabeth (UNSW Sydney, 2006)
Sol-gel matrices may be used to immobilise enzymes, facilitating retention of the catalyst while allowing a flow of substrates and products through the matrix. Candida antarctica lipase B (CALB), a commonly used industrial enzyme, has been shown to have a prolonged catalytic life and enhanced activity when encapsulated in these sol-gel materials. However, the molecular basis for this effect had yet to be elucidated. This study investigated the effect of encapsulating CALB in sol-gel matrices by comparison of CALB in solution with its encapsulated form. Use of complementary techniques revealed the presence of complex interactions between the enzyme and the evolving sol-gel material. 29Si Nuclear Magnetic Resonance (NMR) measurements demonstrated that CALB influenced sol-gel structure by altering silica speciation. Inclusion of CALB also altered the mesoporosity of the matrices as determined using nitrogen sorption and electron microscopy. Correlation of activity assays with 29Si speciation changes indicated that the catalytic activity of the enzyme in solution was directly involved in sol-gel hydrolysis and condensation reactions. Increased specific activity of CALB in the sol-gel aqueous precursor solution resulted in measurable changes in the gel structure of matrices containing 3.1mg of CALB/ml of gel. Small angle neutron scattering (SANS) was used to examine the structure of CALB in solution. The influence of the sol-gel reactants glycerol, sodium fluoride and isopropanol upon the radius of gyration of CALB in solution was determined. SANS was also employed in an investigation of encapsulated CALB molecules which utilised contrast matching of the sol-gel matrix. However, contrast variation studies found that the match point for the silica matrix, both with and without enzyme present, was lower than predicted (~35% vol% D2O). Consequently, the contrast match point of the protein was close to that of the encapsulating material. Scattering from the encapsulated protein at this point was therefore minimal; it is clear that the contrast match point of the protein should be moved through in vivo deuteration in future experiments of this type. These investigations advance the understanding of interactions between the matrix and the encapsulated enzyme in sol-gel biomaterials.